2010
DOI: 10.1007/s10286-010-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical properties of heart rate variability in type 1 diabetes

Abstract: Heart rate variability related to heart rate decelerations and accelerations is reduced in patients with type 1 diabetes compared to healthy individuals both in resting 10-min and ambulatory 24-h ECGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 6 publications
2
30
1
1
Order By: Relevance
“…Similar results were also observed in patients with DM1 ≥40 years of age (8,18), and in young subjects with a mean age of 22 years (34).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were also observed in patients with DM1 ≥40 years of age (8,18), and in young subjects with a mean age of 22 years (34).…”
Section: Discussionsupporting
confidence: 77%
“…In the control group, the visual analysis of Poincaré plot showed a greater beat-to-beat dispersion and long-term RR dispersion which is representative of a normal ANS behaviour (10,16). Similar results were found in studies that also qualitatively analyzed the Poincaré plot in individuals with DM1 (8,18).…”
Section: ) Rr(n) (Ms) On the X-axis And Rr (N+1) (Ms) On The Y-axissupporting
confidence: 83%
“…34 We have also reported on the reduced expression of short-term heart rate asymmetry in patients with type 1 diabetes of long duration of at least 25 years in whom diabetic autonomic neuropathy is a very common finding. 21 Additionally, we have reported on the significant correlation between various measures of heart rate asymmetry and indices of HRV and baroreflex function, but not blood pressure variability. 33 Further, we have described another phenomenon of the asymmetry of systolic blood pressure variability in healthy people, and although short-term heart rate asymmetry was also present in the same persons there was no correlation between both phenomena.…”
Section: Discussionmentioning
confidence: 90%
“…[18][19][20] Heart rate asymmetry, although independent of blood pressure asymmetry, is probably related to baroreflex, which is supported by the observation that heart rate asymmetry is correlated with measures of baroreflex function. 32 Porta et al 33 showed that asymmetrical features of HRV change during sympathetic provocation like head-up tilting and that heart rate asymmetry expression increases during the day compared with night, both in healthy people and patients with congestive heart failure. 17,24 Recently, we showed that heart rate asymmetry is reduced in patients with type 1 diabetes of at least 25-year duration of the disease both in 10-min resting and in 24-h ambulatory Holter ECG recordings.…”
Section: Discussionmentioning
confidence: 99%